Flaubert and the literature of classical antiquity - Goddard, S; Goddard, Stephen (1999)
It has long been recognized that Flaubert took a great deal of interest in the literature of classical antiquity. Contemporaries such as Gautier and Maupassant considered him widely-read; a significant minority of his works - La Tentation de saint Antoine, Salammbô and Hérodias- are set roughly during the classical period; and a number of critics have investigated specific aspects of his debt to antiquity. Generally critics have concentrated on Flaubert's documentary use of the literature of antiquity in the works mentioned above (this is Benedetto's and Seznec's approach) or on the incorporation of mythical imagery and symbolism into his work (this is Lowe's approach in Towards the real Flaubert). A few articles have dealt with specific classical works to which Flaubert may be indebted artistically, but there has been to my knowledge no attempt to define the overall effect upon Flaubert's work, in terms of textual influence or more broadly, of his interest in antiquity. I have attempted in this study to evaluate the impact of the literature of classical antiquity upon Flaubert's entire œuvre. I first attempt to define, mainly by reference to the Correspondance, the extent of his knowledge of classical literature. I then consider his works - juvenilia and adult material - in approximately chronological order in the light of the writers he knew and admired, with a view to suggesting ways in which classical texts may have influenced them; textual influence is investigated closely, but attention is also paid to the use of classical themes, imagery and symbolism. Works with a modern setting are considered as well as those of a more obviously classical pedigree. Having identified a range of authors as being of importance - including Homer, Virgil, Ovid and Apuleius - I conclude by considering more broadly Flaubert's position relative to that of his contemporaries and the overall implications of my findings for the understanding of his work.